The influence of organizational culture on employee performance with work discipline as an intervening variable at PT Bersama Makmur Raharja Padang - Wiharti, Gema; Isnurhadi, Isnurhadi; Hadjri, Muhammad Ichsan (Universitas Wiralodra, 2024)
This study aims to analyze the influence of organizational culture on employee performance with work discipline as an intervening variable at PT Bersama Makmur Raharja Padang. This research uses a quantitative approach. The sample in this study consists of permanent employees of PT Bersama Makmur Raharja Padang, with a population of 111 respondents, and the sample size includes all employees in the population, totaling 111 respondents. The data source for this research is primary data collected through offline questionnaire distribution. The data analysis method in this study uses Structural Equation Modeling (SEM) with the Smart PLS program. The results of this study indicate that organizational culture has a positive and significant effect on employee performance, organizational culture has a positive and significant effect on work discipline, work discipline has a positive and significant effect on employee performance, and organizational culture has a positive and significant effect on employee performance mediated by work discipline.